Webster's collegiate thesaurus - "Webster, Merriam " (Mrrriam Webster Inc. Massachusetts, 1988)
"For the first time in over a century, here is a totally new and different thesaurus which guides the user in seconds to the word needed in a particular situation. Webster's Collegiate Thesaurus provides the user with a wider range of relevant terms without the confusion created by indexes and long lists of undiscriminated words lumped together"--Back cover